2008
DOI: 10.1177/154405910808700108
|View full text |Cite
|
Sign up to set email alerts
|

Butyric Acid Induces Apoptosis in Inflamed Fibroblasts

Abstract: Butyric acid, an extracellular metabolite from periodontopathic bacteria, induces apoptosis in murine and human T- and B-cells, whereas intact gingival fibroblasts isolated from healthy humans are resistant to butyric-acid-induced apoptosis. We examined the susceptibility of inflamed gingival fibroblasts isolated from adult persons with periodontitis to butyric-acid-induced apoptosis. Butyric acid significantly suppressed the viability of inflamed gingival fibroblasts and induced apoptosis in a dose-dependent … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
77
2
2

Year Published

2009
2009
2024
2024

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 93 publications
(87 citation statements)
references
References 22 publications
1
77
2
2
Order By: Relevance
“…These findings suggested that the active component contained in csp could be a heat sensitive, volatile, low-molecular-mass (Ͻ3000 Da) component. In addition, it was previously reported that the extracellularly secreted SCFA species of P. gingivalis, most likely butyric acid, could be involved in periodontal diseases (48,49). Moreover, the presence of high concentrations of butyric acid in periodontal pockets was demonstrated by others (50,51).…”
Section: Involvement Of Butyric Acid In the Reactivation Of Latent Hiv-1mentioning
confidence: 95%
“…These findings suggested that the active component contained in csp could be a heat sensitive, volatile, low-molecular-mass (Ͻ3000 Da) component. In addition, it was previously reported that the extracellularly secreted SCFA species of P. gingivalis, most likely butyric acid, could be involved in periodontal diseases (48,49). Moreover, the presence of high concentrations of butyric acid in periodontal pockets was demonstrated by others (50,51).…”
Section: Involvement Of Butyric Acid In the Reactivation Of Latent Hiv-1mentioning
confidence: 95%
“…Previous published works related to our group have shown that BA induces apoptosis in inflamed fibroblasts (Kurita-Ochiai et al 2008), Jurkat T cells (Kurita-Ochiai et al 1997;KuritaOchiai and Ochiai 2010), human peripheral blood mononuclear cells (Kurita-Ochiai et al 1999), WEHI 231 and RAJI B-lymphoma cells (Kurita-Ochiai et al 1998), splenic T cells and B cells (Kurita-Ochiai et al 1997, and murine thymocytes (Kurita-Ochiai et al 1997).…”
Section: Introductionmentioning
confidence: 99%
“…AOP at 78 kDa was predominantly detected in the periplasm/outer membrane and cytosol fractions. When the periplasmic/outer membrane fraction was subjected to size exclusion HPLC, 78-kDa AOP was detected as a monomer at fractions [23][24][25][26]. Because the cytosolic preparation contained a considerable amount of periplasmic components, P. gingivalis AOP appears to be primarily distributed in the periplasm and present mainly as a monomer in cells.…”
mentioning
confidence: 99%
“…extracellular and outer membrane-bound Rgp/Kgp and DPPs/PTP-A in the periplasmic space) appears to be suitable for an ordered degradation of proteinaceous substrates and their incorporation into cells. Through amino acid metabolism, the organism excretes sulfide, ammonia, butyrate (18,19), and methyl mercaptan (20) as end products, which have been suggested to cause host tissue damage (21)(22)(23). Accordingly, DPPs, PTP-A, and gingipains are considered to play crucial roles not only in cell growth but also bacterial pathogenicity.…”
mentioning
confidence: 99%